Embedded system for biometric identification based on iris detection - Ahmad Nasir, Che Rosli; R. Badlishah, Ahmad; Ali Yeon, Md Shakaff; Mohamad Rizon, Mohamed Juhari (Institute of Electrical and Electronics Engineering (IEEE), 2009)
Link to publisher's homepage at http://ieeexplore.ieee.org